Irresistible [videorecording (DVD)] - Stewart, Jon, 1962-; Carell, Steve, 1962-; Cooper, Chris, 1951-; Davis, Mackenzie; Grace, Topher, 1978-; Byrne, Rose (Universal Pictures Home Entertainment, 2020)
A Democratic strategist assists a retired veteran run for mayor in a small, conservative Midwest town.